PERAN KEPEMIMPINAN STRATEGIS PADA SEKTOR UMKM TERHADAP HUBUNGAN KETERAMPILAN WIRAUSAHA DAN MOTIVASI BERWIRAUSAHA TERHADAP KINERJA BISNIS - Maryadi, Adi; Hermiati, Novi Fitria; Purnamasari, Pupung; Afandi, Dian Rachmawati; Kosim, Muhammad (Universitas Nusa Cendana, 2024)
This study aims to examine how strategic leadership in the MSME sector affects the relationship between entrepreneurial skills and entrepreneurial motivation to business outcomes. The selection of respondents for this study will be conducted by random sampling and purposive sampling for owners and leaders of MSMEs in Central Cikarang. A total of 100 respondents will be selected as the sample size. To conduct data analysis will use the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that entrepreneurial motivation does not directly influence business performance, but entrepreneurial ability and strategic leadership have a significant relationship with business performance. In addition, strategic leadership was shown to regulate the relationship by enhancing the positive effects of entrepreneurial ability and motivation on business outcomes. These findings emphasize the importance of strategic leadership development in improving the performance and survival of MSMEs Keywords: Entrepreneurial Skills; Entrepreneurial Motivation; Strategic Leadership; Business Performance